Flavonoid‐Rich Apple Improves Endothelial Function in Individuals at Risk for Cardiovascular Disease: A Randomized Controlled Clinical Trial. Issue 3 (19th December 2017) - Bondonno, Nicola P.; Bondonno, Catherine P.; Blekkenhorst, Lauren C.; Considine, Michael J.; Maghzal, Ghassan; Stocker, Roland; Woodman, Richard J.; Ward, Natalie C.; Hodgson, Jonathan M.; Croft, Kevin D.
Abstract : Scope: The cardioprotective effects of apples are primarily attributed to flavonoids, found predominantly in the skin. This study aimed to determine if acute and/or chronic (4 weeks) ingestion of flavonoid‐rich apples improves endothelial function, blood pressure (BP), and arterial stiffness in individuals at risk for cardiovascular diseases (CVD). Methods and results: In this randomized, controlled cross‐over trial, acute and 4 week intake of apple with skin (high flavonoid apple, HFA) is compared to intake of apple flesh only (low flavonoid apple, LFA) in 30 participants. The primary outcome is endothelial function assessed using flow‐mediated dilation (FMD) of the brachial artery, while main secondary outcomes are 24 h ambulatory BP and arterial stiffness. Other outcomes include fasting serum glucose and lipoprotein profile, plasma heme oxygenase‐1 (Hmox‐1), F2 ‐isoprostanes, flavonoid metabolites, and plasma and salivary nitrate (NO3 − ) and nitrite (NO2 − ) concentrations. Compared to LFA control, the HFA results in a significant increase in FMD acutely (0.8%, p  < 0.001) and after 4 weeks chronic intake (0.5%, p  < 0.001), and in plasma flavonoid metabolites ( p  < 0.0001). Other outcomes are not altered significantly. Conclusion: A lower risk of CVD with higher apple consumption could be mediated by the beneficial effect of apple skin on endothelial function, both acutely and chronically. Abstract : In this randomized, controlled cross‐over study, changes in vascular function were assessed after acute (2 hours) and chronic (4 weeks) ingestion of a high‐flavonoid apple treatment (apple + skin) compared to a low‐flavonoid apple control (apple flesh only). An improvement in vascular function was only seen after the high‐flavonoid apple treatment, providing evidence for the theory that the cardiovascular health benefits of apples are, at least in part, attributable to the high concentration of flavonoids found in apple skin.